Late diagnosis of Hashimoto's thyroiditis and its serious clinical repercussions: Case report (Research, Society and Development, 2024)
Hashimoto's Thyroiditis is an autoimmune disease, characterized by lymphoplasmic infiltration and atrophy of the thyroid parenchyma, resulting in the decrease or loss of activity of the gland, caused by the presence of antibodies with thyroid antigens. The diagnosis is made through common clinical manifestations, elevated TSH and reduced hormonal activity of the gland with autoantibody positivity. Treatment consists of replacing thyroxine through medication.  Late clinical manifestations, such as failure to thrive and cavity effusions, are serious and rare manifestations observed in patients with late diagnosis. The study aims to report the clinical case of a pediatric patient with a late diagnosis of Hashimoto's Thyroiditis and its serious clinical repercussions in the Pediatric Endocrinology service of the Maria Aparecida Pedrossian University Hospital, using electronic medical records and complementary exams performed by the patient. Its purpose is to highlight the importance of early diagnosis of the disease for a better prognosis and quality of life for patients.